New synonymy and two new species of Caucasian moth flies (Diptera, Psychodidae, Psychodinae) from Azerbaijan and Georgia - Ježek, Jan; Oboňa, Jozef; Manko, Peter (European Journal of Taxonomy, 2022)
Psychodid specimens from one of the world’s biodiversity hotspots – the Caucasus region – were sorted from samples collected during field work in 2019. Pneumia fuehzulii sp. nov. (from two localities in Azerbaijan) and Thornburghiella salihi sp. nov. (from one locality in Azerbaijan and four sites in Georgia) are described from this material. Differential diagnoses are given and some morphological characters illustrated. Sijaricia Krek, 1999, syn. nov. of Thornburghiella Vaillant, 1982 is proposed and T. erinacea (Krek, 1971) comb. nov. from Ulomyia Walker, 1856 is suggested.